Dynamics of Volatility Spillover between Energy and Environmental, Social and Sustainable Indices - Babu, Manivannan; Lourdesraj, A. Antony; Hariharan, C.; Jayapal, Gayathri; Indhumathi, G.; Sathya, J.; Kathiravan, Chinnadurai (International Journal of Energy Economics and Policy, 2022)
The purpose of this research was to examine the dynamics of volatility spillover between energy and environmental, social, and sustainable indices. COVID19 prompted the research to select April 2019 to March 2022 as a sample period, and the respective data (Daily Prices) of the Nifty Energy and Nifty ESG indices were obtained from the National Stock Exchange of India Limited. The outcomes of the study confirmed that the daily returns of Nifty Energy and Nifty 100 ESG indices were not normally distributed and reached stationarity at level difference. Further, the study employed GARCH Models such as ARCH, GARCH (1,1), and GARCH-M to determine conditional volatility, and it validated the ARCH influence on the daily returns of the Nifty Energy and Nifty 100 ESG, during the study period